NEGOSIASI IDENTITAS DAN GLOKALISASI EKONOMI: STRATEGI ADAPTASI WARUNG MADURA DI TENGAH HEGEMONI RITEL MODERN DAN BUDAYA LOKAL BALI - I Nyoman Satria Pritanjaya; I Gede Andi Legawa (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
The rapid growth of modern minimarkets and the continued presence of local grocery stores have created increasingly intense competition among small-scale businesses. This study aims to understand the adaptation strategies employed by Warung Madura in responding to competition from modern minimarkets and local grocery stores in Sanur Kaja Village, Denpasar City, based on John William Bennett’s theory of adaptation. Data were collected using a qualitative approach, which is a hallmark of anthropological research, through observation, interviews, and literature studies. The findings reveal that Warung Madura applies various forms of adaptive strategies to maintain its existence. These include adjusting its product offerings to meet local needs and cultural practices, such as selling arak (traditional liquor) and incense, practicing service ethics through friendliness and the use of the Balinese language in customer interactions, and adapting to technological developments by implementing digital payment systems such as QRIS and e-wallets. In addition, business owners demonstrate respect for local customs and values by participating in social activities and adhering to village regulations. From the community’s perspective, perceptions of Warung Madura are divided into two categories: positive and selective. Positive perceptions arise because the community views Warung Madura as offering accessibility, competitive prices, and good service. Meanwhile, selective perceptions are held by those who prefer shopping at minimarkets or local grocery stores but still choose Warung Madura as an alternative when necessary.